High expression levels of ras p21 protein in normal mouse heart tissues. Issue 12 (December 1985) - Spandidos, Demetrios A.; Dimitrov, Todor
Abstract : We have investigated the levels of protein encoded by the rat oncogene in normal mouse tissues using an immunoblotting technique. We have found that heart from young or adult NIH or Balb C strains of mice contain high levels of rat protein as compared to lung, liver, spleen, kidney, brain and skeletal muscle tissues from the same animal. Our results indicate that cellular rat expression does not in every case correlate with cell proliferation.